Investigating the impact of dioxins, furans, and coplanar polychlorinated biphenyls on mortality, inflammatory states, and chronic diseases: An integrative epidemiological analysis - Jiaxing Tan; Ying Gao; Yuanlin Xia; Peiyan Sun; Wei Qin (Ecotoxicology and Environmental Safety)
Several organic pollutants, including dioxins, furans, and coplanar polychlorinated biphenyls (PCBs), have become a growing concern due to their significant capacity for accumulation and migration across regions, as well as their extended half-lives and relatively high toxicity. Our study aimed to assess the impact of these pollutants on mortality, inflammatory states, and chronic diseases. Exposure was quantified in serum through high-resolution gas chromatography and isotope-dilution high-resolution mass spectrometry. Statistical analyses employed multivariate Cox regression, multivariate logistic regression, restricted cubic splines and subgroup analysis. The results indicated a significant increase in mortality (p < 0.05) associated with the seven substances classified as dioxins, furans, and PCBs. Moreover, these pollutants were linked to a higher incidence of chronic diseases, including hematological disorders, chronic kidney disease, hypertension, and diabetes (p < 0.05). Additionally, a robust correlation was observed between serum C-reactive protein (CRP) and neutrophil-to-lymphocyte ratio (NLR) concentrations and these substances, revealing their proinflammatory effects at specific concentrations. Consequently, our research unmasked that exposure to dioxins, furans, and coplanar PCBs could be associated with an elevated mortality rate, increased inflammatory conditions, and a higher incidence of chronic diseases. We proposed that exposure to these pollutants may initiate various afflictions by activating the inflammatory system, ultimately resulting in increased mortality. However, this hypothesis requires further empirical investigation to validate its assertions.